Managing Achilles Tendinopathy: Current Evidence and Modern Strategies - Wrzesinska, Amadea; Korowacki, Mateusz; Rusin, Iga; Kazimierczak, Karol; Mączka, Krystian; Kruczek, Filip; Dyczko, Jakub; Świrad, Bartosz; Przybylski, Michał; Grobecki, Daniel (Quality in Sport, 2026)
Introduction: Achilles tendon tendinopathy is a common degenerative disorder causing pain and functional limitation. Despite numerous treatment options, optimal management remains a clinical challenge. Aim: To summarize current evidence on the pathophysiology, diagnosis, conservative treatment, modern adjunctive therapies, and surgical management of Achilles tendon tendinopathy . Materials and methods: This narrative review is based on scientific literature, including guidelines, systematic reviews, and clinical studies. Particular attention was paid to diagnostic methods, progressive rehabilitation, extracorporeal shockwave therapy (ESWT), injections (PRP, hyaluronic acid, high-volume), fenestration, stem cells, and surgery. Results: Diagnosis is primarily clinical, with ultrasound and MRI reserved for unclear or resistant cases. Conservative treatment is the first-line approach, focusing on load management and structured rehabilitation (e.g., the Alfredson protocol). Modern adjunctive therapies and injections may provide benefits, though evidence quality varies. Surgical treatment is reserved for persistent cases failing conservative therapy. Conclusions: Effective management requires an individualized, multidisciplinary approach centered on patient education, load modification, and evidence-based rehabilitation. Biological and minimally invasive therapies serve as adjuncts, but further high-quality studies are needed